An industrial case study for adopting software product lines in automotive industry an evolution-based approach for software product lines (EVOA-SPL) - Ignaim, Karam (2019)
Software Product Lines (SPLs) seek to achieve gains in productivity and time to market. Many companies in several domains are constantly adopting SPLs. Dealing with SPLs begin after companies find themselves with successful variants of a product in a particular domain. The adoption of an SPL-based approach in the automotive industry may provide a significant return on investment. To switch to an SPL-based approach, practitioners lack a reengineering approach that supports SPL migration and evolution in a systematic fashion. This paper presents a practical evolution-based approach to migrate and evolve a set of variants of a given product into an SPL and describes a case study from the automotive domain. The case study considers the need to handle the classical sensor variants family (CSVF) at Bosch Company. Using this study, we performed a contributed step toward future switch of the CSVF into the SPL. We investigated the applicability of the proposed evolution-based approach with a real variants family (using the textual requirements of the CSVF) and we evaluated our approach using several data collection methods. The results reveal that our approach can be suitable for the automotive domain in the case study.